An 8/6 SRM drive with a multilevel topology based on a cross-switched configuration - Fernao Pires, Vitor (2020)
SRM drives based on multilevel power electronic converter presents several advantages, like reducing the switching frequency and improve the operation of the motor under high speed. In this way, several multilevel power converter topologies have been developed for the SRM drives. In line with this, this paper proposes a new multilevel power converter topology for the 8/6 SRM drive. The topology was developed with the purpose to reduce the number of power semiconductors, without reducing the performance of the motor. The proposed topology was designed in a way that uses crossover switches. The operation of the power converter topology in all of their modes is analyzed in a detailed way. The verification of the global system performance (drive and motor) is realized by the implementation of simulation studies. Indeed, through these studies it is verified that at low speed operation the switching frequency is reduced, but maintaining the application of the maximum voltage during the magnetization and demagnetization process.